PEMBINAAN MENTAL AGAMA DALAM MEMBENTUK KEPRIBADIAN MUSLIM PRAJURIT DI MASJID AR-RIDHA KOMPLEK ANGKATAN LAUT BARAKUDA - Saiful Akhyar Lubis; Abdurrahman Abdurrahman; Arya Prandana (JP : JURNAL PENDIDIKAN, 2021)
Abstract: This study aims to determine the implementation of religious mental coaching in shaping the personality of Musxii lim soldiers in the Ar-Ridha Mosque, Barracuda Navy Complex. This study uses the type of Ex Post Facto research because the independent variables in this study are not controlled or specially treated but only reveal facts based on the measurement of the symptoms that have existed in the respondent before this research was conducted. This study uses a descriptive qualitative approach, namely by systema-tically carrying out descriptions, descriptions or paintings that have been processed into a sentence in testing hypotheses and knowing factual and accurate data about events or activities, characteristics and relationships between the phenomena being investigated.The results showed that: The implement-tation of religious mental guidance at the Ar-Ridha Mosque, Barracuda Navy Complex, is carried out routinely every Wednesday morning at 08.00 until finished at the ar-Ridha Mosque. Forms of Religious Mental Development are specified in various forms, such as: Forms of Guidance, Forms of Guidance. Forms of counseling, forms of service, and forms of care. The material for religious mental development activities is Islamic material that covers all aspects of life in accordance with the qur’an and Hadith, while the methods for religious mental development activities are diverse, namely lectures, question and answer, discussion, and recitation. The results of Religious Mental Development show that this religious mental development activity has good results for soldiers.Keywords: development, mental, personality, soldier.